Reducing Adverse Drug Reactions for Older People in the Community: Evaluating the Validity and Reliability of the ADRe Profile - Logan, Vera; Carter, Neil; Hughes, David; Turner, Adam; Jordan, Sue (Journal of nursing management)
Background: Adverse drug reactions (ADRs), particularly in the context of polypharmacy, remain a persistent, unresolved problem for patients and healthcare professionals. The ADRe Profile identifies medicine‐related harms, and supports their resolution, thereby improving care quality and preventing future problems. Objective: The objective of this study was to assess the validity and reliability of the ADRe Profile ( https://www.swansea.ac.uk/adre/ ) in U.K. primary care general practices, building on assessments in other settings. Methods: The ADRe Profile’s validity and reliability were investigated using complementary mixed methods: content validity index, contrast group construct validity, cognitive interviewing, and inter‐rater reliability. Results: Cognitive interviews ( n = 5) confirmed that the ADRe Profile needed only minor adjustments. The scale‐level content validity index was 0.67 ( n = 14), items ranging from 0.08 to 1. Significant differences in signs and symptoms associated with ADRs between service users taking different numbers of regular prescribed medicines confirmed construct validity ( n = 68, U = 870.50, p < 0.001). Inter‐rater reliability testing showed substantial agreement between service users and research nurse: 10 items had 100% agreement. Overall kappa mean was 0.71 (range: 0.31–1), ( n = 42). Conclusions and Relevance: The ADRe Profile is suitable for use with older service users in primary care who live at home. Users understood the questions and provided meaningful answers. ADRe Profile responses were sufficiently reliable to be used as a basis for further investigations, prescriber referral and clinical actions. However, clinician judgement of content validity may depend on knowledge and experience, highlighting the importance of training. Clinicians acknowledged that the ADRe Profile was comprehensive but identified practical difficulties. Instruments to reduce ADRs should be validated before testing in feasibility studies and randomised controlled trials. Implications for Nursing Management: Managers need to optimise patient safety by introducing patient‐centred symptom monitoring, with decision support. Before instruments are adopted, managers should check the reliability and validity data. Trial Registration: ClinicalTrials.gov identifier: NCT04663360